The media economy - Albarran, Alan B. (New York Routledge, 2010)
The Media Economy analyzes the media industries and their activities from macro- to micro-levels, using concepts and theories to demonstrate the role the media plays in the economy as a whole. Representing a rapidly changing and evolving environment, this text breaks new ground through its analysis from two unique perspectives:

-examining the media industries from a holistic perspective by analyzing how they function across different levels of society (global, national, household, and individual);
-looking at the key forces (technology, globalization, regulation, and social aspects) constantly evolving and influencing the media industries.

It includes examples from both developed and developing nations, as well as data and trends from these countries, offering a broad arena of study.

Key features of this innovative text include:

-topics new to media economics texts, such as finance and investment, labor, and social aspects;
-accessible discussion of complicated concepts and their application to media industries;
-new directions for both theoretical and methodological areas.

With the media industries in an ongoing state of change and transformation, The Media Economy offers new reference points for the field to consider when defining and analyzing media markets. It will be essential reading for students and practitioners in media management and economics who need to understand the role of media in the global economy.
Understanding the media economy -- Theories and approaches used to examine the media economy -- Key concepts to understand the media economy -- Evolving markets in the media economy -- Multi-platform media enterprises -- Technology and the media economy -- Globalization and the media economy -- Regulation and the media economy -- Social aspects of the media economy -- Finance, valuation, and investment in the media economy -- Labor and the media economy -- Assessing the future of the media economy.
Includes bibliographical references (pages 183-190) and index (pages 191-202).
CMC-2637 donated by Ms. Christine Muyco.
Keywords: Mass media -- Economic aspects